Talent allocation in the school-to-job transition - Francesco Chelli; Luisa Rosti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2004)
This paper raises the problem of the optimal allocation of talent in a gendered perspective. It analyses the transition from education to labor market in Italy, and the way in which gender differences emerge early in the labor market career. Our data establish higher grades for females in both male and female type of courses on the one hand, and lower employment rate, lower entry wages, and under-representation in apical positions for women three years after graduation on the other. We explain female educational over-performance by means of signaling theory and under-utilization of female manpower by means of tournaments theory.
Keywords: J24; I21; J16; 330; Analysis of Education; Human Capital; Economics-of-Gender; Humankapital; Geschlecht; Italien; Arbeitsmarktintegration